Migrant nurses and care workers rights in Canada - Bukola Salami; Oluwakemi Amodu; Philomena Okeke-Ihejirika (United Nations Research Institute for Social Development (UNRISD), 2016)
Between 2000 and 2014, there was increasing mobility of migrant workers to Canada, especially through temporary migration streams. However, the large expansion of the Canadian Temporary Foreign Worker Program from 2000 to 2014 has been curtailed over the last one to two years with more restrictive policies. In this paper, we will discuss care worker rights within the changing policy landscape in Canada, with a focus on individuals who migrate as domestic caregivers and as nurses. The paper illustrates the systemic barriers to the enforcement of rights and access to the profession for nurses who migrate to Canada as migrant caregivers. It finds that the Canadian government has restricted access to citizenship rights for some groups of care workers, increased the role of employers in the selection of immigrants to Canada, and created a pathway for skilled healthcare professionals to migrate to Canada through the Canada Caregiver Program. This has made their legal status in Canada more precarious as healthcare professionals who migrate through the Canada Caregiver Program must now first reside in Canada for two years and meet specific eligibility requirements before becoming a permanent resident in the country.
Additional information: Addressing Multiple Forms of Migrant Precarity: Beyond “Management” of Migration to an Integrated Rights-Based Approach
Keywords: 330